Cover Picture: Synthesis and Evaluation of Novel Acyclic Nucleoside Phosphonates as Inhibitors of Plasmodium falciparum and Human 6‐Oxopurine Phosphoribosyltransferases (ChemMedChem 10/2015). Issue 10 (October 2015) - Kaiser, Martin M.; Hocková, Dana; Wang, Tzu‐Hsuan; Dračínský, Martin; Poštová‐Slavětínská, Lenka; Procházková, Eliška; Edstein, Michael D.; Chavchich, Marina; Keough, Dianne T.; Guddat, Luke W.; Janeba, Zlatko
<x xml:space="preserve">Abstract</x> The front cover picture shows the crystal structure of the active site of human hypoxanthine–guanine phosphoribosyltransferase (HGPRT) in complex with (S)‐3‐hydroxy‐2‐(phosphonoethoxy)propylguanine (HPEPG). HPEPG exhibits high potency for the hypoxanthine‐guanine‐xanthine phosphoribosyltransferase (HGXPRT) of Plasmodium falciparum (Ki = 0.1 μM), as well as for human HGPRT (Ki = 0.6 μM). The crystal structures of acyclic nucleoside phosphonates (ANPs), including HPEPG, in complex with human HGPRT reveal the binding mode of novel inhibitors and show specific interactions with active site residues. Such information is important for future design of more potent inhibitors of plasmodial 6‐oxopurine phosphoribosyltransferases. This approach may represent a viable strategy to treat malaria. More details can be found in the Full Paper by Luke W. Guddat, Zlatko Janeba et al. on page 1707 in Issue 10, 2015. (DOI: 10.1002/cmdc.201500322).